2020
DOI: 10.1108/gkmc-04-2020-0048
|View full text |Cite
|
Sign up to set email alerts
|

Impact of students personality traits on social networking sites usage, benefits and risks

Abstract: Purpose This study aims to explore the personality traits (agreeableness, extraversion, conscientiousness, openness to experience and neuroticism) of the students. The differences among the personality traits of students toward social networking sites (SNS) usage, benefits and risks are also analyzed. Design/methodology/approach Two instruments including; BFI scale and self-structured instrument, were administered to collect data. Kruskal–Wallis test was applied to determine the differences between the perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Age negatively correlates with users' awareness of others' improved social network search techniques. Data showed that students' perceptions of social network influence matched the actual effects [20].…”
Section: Discussionmentioning
confidence: 86%
“…Age negatively correlates with users' awareness of others' improved social network search techniques. Data showed that students' perceptions of social network influence matched the actual effects [20].…”
Section: Discussionmentioning
confidence: 86%
“…It is because, apart from these independent factors, other uncontrollable variables can make anyone a smartphone user, regardless of their psychic attributes. Ahmed et al (2021), while studying students' personality traits on social networking sites usage, benefits, and risks in Pakistan, found that individuals with the extraversion trait are more likely to use social media negatively. In contrast, individuals with the conscientiousness trait are more likely to use social media moderately and positively impact their health, education, and everyday life.…”
Section: Personality and Motivations To Use Social Mediamentioning
confidence: 99%
“…Conscientious people did their job in an orderly and efficient manner (Carvalho et al, 2020). Besides, Ahmed et al (2020) have mentioned that Conscientious people appear to display self-discipline, behave obediently, and strive for accomplishment. Those people also show organised actions rather than spontaneous and they are generally reliable (Abe, 2020).…”
Section: The Big Five Personality Traitsmentioning
confidence: 99%
“…Extraversion people seem to love and be enthusiastic, actively discuss, assertive, and gregarious about human interactions (Abe, 2020). While Ahmed et al (2020) stated that they are excited and doing well around other individuals as well as tend to work well in groups. Camadan et al (2018) emphasised an Extraversion person is likely to enjoy spending their valuable time with others rather than be rewarded although they are known to be reserve.…”
Section: The Big Five Personality Traitsmentioning
confidence: 99%
See 1 more Smart Citation